Access to Safe Drinking Water and WASH Facilities in Schools of District Chiniot, Pakistan and Awareness on Waterborne Diseases among Teachers and Students - Bashir Ahmed Tahir; Mirza Naseer Ahmad; Rashida Sultana (International Journal of Economic and Environmental Geology, 2018)
This study assessed the situation of safe drinking water, health and hygiene conditions, and knowledge about waterborne diseases among the teachers and students of 153 selected government and private schools in District Chiniot, Pakistan. The methodology relied on questionnaires and discussion with the school teachers and students. In the survey sample, a total of 153 schools of Tehsil Lalian, District Chiniot, were included. While, total 306 Head Teachers and students of the selected schools including 153 head teachers (males 34 and females 119) and 153 students (boys 62 and girls 91), were interviewed for data collection. The quantitative and qualitative data on the issues related to safe drinking water, WASH (water, sanitation and hygiene) facilities, and waterborne diseases were collected and analyzed using SPSS (Statistical Package for the Social Sciences). The study revealed that the main sources of drinking water in the schools were hand pumps (73%) and about 80% schools have sufficient quantity of available water throughout year. More than 90% head teachers and 92% students reported that water has no smell and color but it has a specific taste. About 86% head teachers and 38% students were not satisfied with existing drinking water services. As reported by 100% respondents, schools have toilets, while 95% students confirmed that students waste water in the schools. Students were asked about the disposal of used water in their schools and in their homes. In response, 23% students said that used water was properly disposed in their schools, while only 10% students told that used water was properly disposed in their homes. 100% teachers and students have knowledge about the diseases caused by drinking unsafe water, but sometimes they don’t take care in using water. About 68% head teachers told that no water treatment methods were used by the people in the area. Lack of knowledge and affordability were the main reasons for not using the water treatment methods. The need for promotion of knowledge among the teachers and students on use of safe drinking water and to improve health and hygiene conditions in schools and homes was also emphasized.